Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Deciphering Post-surgery Gut Microbial Dynamics in Colorectal Cancer through Multi-cohort Machine Learning - Mutebi John Kenneth; Chin-Chia Wu; Chuan-Yin Fang; Michael W. Y. Chan; Bing-Mu Hsu (Current Microbiology, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Substantial discrepancies across global fire emissions inventories: a systematic intercomparison - Jiyuan Yang; Hanyue Zheng; Peng Zhao; Johannes W. Kaiser; Qing Mu (Journal of Environmental Sciences, 2026)

Underestimated small thermokarst lakes of the Qinghai-Tibet Plateau and their carbon emission potential - Xiaoqing Peng; Hengxing Luo; Weiwei Tian; Zhuoxuan Xia; Oliver W. Frauenfeld; Cuicui Mu; Lin Liu; Jing Luo; Lingcao Huang; Qinshan Zhao; Yimiao Yin (Global and Planetary Change, 2026)

The moon's formation time recorded in lunar mare basalts - Mu-Han Yang; Qian W.L. Zhang; Richard W. Carlson; Bi-Wen Wang; Dongjian Ouyang; Qiu-Li Li (Icarus, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Predicting internal carotid artery system risk based on common carotid artery by machine learning - Yuhao Tong; Qingyi Zhang; Feng Zhang; Weidong Mu; Steven W. Su; Lin Liu (Medical & Biological Engineering & Computing, 2025)

2.2-billion-year-old KREEP-rich volcanism on the Moon - Mu-Han Yang; Qian W.L. Zhang; Qiu-Li Li; Ross N. Mitchell; Richard W. Carlson; Zhu-Yin Chu; Yu Liu; Yi Chen; Shun Guo; Ding-Shuai Xue; Bin Su; Xu Tang; et al. (Science Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Data driven food fraud vulnerability assessment using Bayesian Network: Spices supply chain - Y. Bouzembrak; N. Liu; W. Mu; A. Gavai; L. Manning; F. Butler; H.J.P. Marvin (Food Control, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Linking carbon cycle perturbations to the Late Ordovician glaciation and mass extinction: A modeling approach - Junpeng Zhang; Chao Li; Yangyang Zhong; Xuejin Wu; Xiang Fang; Mu Liu; Daizhao Chen; Benjamin C. Gill; Thomas J. Algeo; Timothy W. Lyons; Yuandong Zhang; Hui Tian (Earth and Planetary Science Letters, 2024)

Genome-wide identification of GATA transcription factor family and the effect of different light quality on the accumulation of terpenoid indole alkaloids in Uncaria rhynchophylla - Yingying Shao; Yu Zhou; Li Yang; Detian Mu; Iain W. Wilson; Yao Zhang; Lina Zhu; Xinghui Liu; Ling Luo; Jialong He; Deyou Qiu; Qi Tang (Plant Molecular Biology, 2024)

The infrastructure cost of permafrost degradation for the Northern Hemisphere - Haodong Jin; Xiaoqing Peng; Oliver W. Frauenfeld; Yuan Huang; Lei Guo; Jing Luo; Guoan Yin; Guohui Zhao; Cuicui Mu (Global Environmental Change, 2024)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Biofilm colonization of stone materials from an Australian outdoor sculpture: Importance of geometry and exposure - Cristina Cattò; Andre Mu; John W. Moreau; Nancy Wang; Francesca Cappitelli; Richard Strugnell (Journal of Environmental Management, 2023)

The COMT gene modulates the relationship between bilingual adaptation in executive function and decision-making: an EEG study - Dongxue Liu; John W. Schwieter; Wenxin Liu; Li Mu; Huanhuan Liu (Cognitive Neurodynamics, 2023)

Performance and changes of high‐resolution (1 km) surface air temperature in Northern Hemisphere permafrost regions - Haodong Jin; Xiaoqing Peng; Oliver W. Frauenfeld; Yaohua Zhao; Xuanjia Li; Weiwei Tian; Cong Chen; Benben Liang; Xiaodong Li; Cuicui Mu (International Journal of Climatology, 2023)
Surface air temperatures are significant indicators of environmental and climatic change that affect a diverse set of physical systems including permafrost. Most temperature products, such as gridded or reanalysis data, are still at a relatively low spatial resolution, limiting the ability to simulate heterogeneous permafrost changes and leading to large uncertainties. Here we apply a downscaling method based on elevation to obtain high‐resolution surface air temperatures from the sixth Coupled Model Intercomparison Project in Northern Hemisphere permafrost regions. Root‐mean‐square errors and mean absolute errors after downscaling are reduced by 34 and 37%, respectively, relative to meteorological site data and gridded observations from the Climatic Research Unit. Compared to the downscaled surface air temperature data, nondownscaled model projections overestimate by 0.12–0.39°C in the discontinuous, isolated, and sporadic permafrost regions and underestimate up to 0.18°C in the continuous permafrost region under different emission scenarios. The warming rates in Northern Hemisphere permafrost regions were 0.093°C/10 year during the historical (1850–2014) period and are projected to be 0.22°C/10 year for SSP1‐2.6, 0.48°C/10 year for SSP2‐4.5, 0.75°C/10 year for SSP3‐7.0, and 0.95°C/10 year for SSP5‐8.5 during 2015–2100, which is 1.4–1.6 times the warming of nonpermafrost regions. Warming rates in high latitudes are 1.2–1.7 times higher than those in high‐elevation regions. Continuous permafrost regions' warming will be 1.2–1.4 times higher than in other permafrost regions. For permafrost with high ground ice content, warming will be 1.1 times greater than in permafrost regions with medium or low ground ice content.

Biophysical Reviews special issue call: quantitative methods to decipher cellular heterogeneity — from single-cell to spatial omic methods - Joshua W. K. Ho; Xi Chen; Mu He; Yuanhua Huang; Jessica C. Mar; David J. H. Shih; Angela R. Wu (Biophysical Reviews, 2022)

Identifying areas at risk of drought‐induced tree mortality across South‐Eastern Australia - Martin G. De Kauwe; Belinda E. Medlyn; Anna M. Ukkola; Mengyuan Mu; Manon E. B. Sabot; Andrew J. Pitman; Patrick Meir; Lucas A. Cernusak; Sami W. Rifai; Brendan Choat; David T. Tissue; Chris J. Blackman; et al. (Global Change Biology, 2020)
South‐East Australia has recently been subjected to two of the worst droughts in the historical record (Millennium Drought, 2000–2009 and Big Dry, 2017–2019). Unfortunately, a lack of forest monitoring has made it difficult to determine whether widespread tree mortality has resulted from these droughts. Anecdotal observations suggest the Big Dry may have led to more significant tree mortality than the Millennium drought. Critically, to be able to robustly project future expected climate change effects on Australian vegetation, we need to assess the vulnerability of Australian trees to drought. Here we implemented a model of plant hydraulics into the Community Atmosphere Biosphere Land Exchange (CABLE) land surface model. We parameterized the drought response behaviour of five broad vegetation types, based on a common garden dry‐down experiment with species originating across a rainfall gradient (188–1,125 mm/year) across South‐East Australia. The new hydraulics model significantly improved (~35%–45% reduction in root mean square error) CABLE’s previous predictions of latent heat fluxes during periods of water stress at two eddy covariance sites in Australia. Landscape‐scale predictions of the greatest percentage loss of hydraulic conductivity (PLC) of about 40%–60%, were broadly consistent with satellite estimates of regions of the greatest change in both droughts. In neither drought did CABLE predict that trees would have reached critical PLC in widespread areas (i.e. it projected a low mortality risk), although the model highlighted critical levels near the desert regions of South‐East Australia where few trees live. Overall, our experimentally constrained model results imply significant resilience to drought conferred by hydraulic function, but also highlight critical data and scientific gaps. Our approach presents a promising avenue to integrate experimental data and make regional‐scale predictions of potential drought‐induced hydraulic failure.

WormBot, an open-source robotics platform for survival and behavior analysis in C. elegans - Jason N. Pitt; Nolan L. Strait; Elena M. Vayndorf; Benjamin W. Blue; Christina H. Tran; Brendon E. M. Davis; Karen Huang; Brock J. Johnson; Keong Mu Lim; Sophie Liu; Arash Nikjoo; Anuj Vaid; et al. (GeroScience, 2019)

Repurposed FDA-approved drugs targeting genes influencing aging can extend lifespan and healthspan in rotifers - Terry W. Snell; Rachel K. Johnston; Amelia B. Matthews; Hongyi Zhou; Mu Gao; Jeffrey Skolnick (Biogerontology, 2018)

Baseline results from the UK SIGNIFY study: a whole-body MRI screening study in TP53 mutation carriers and matched controls - Sibel Saya; Emma Killick; Sarah Thomas; Natalie Taylor; Elizabeth K. Bancroft; Jeanette Rothwell; Sarah Benafif; Alexander Dias; Christos Mikropoulos; Jenny Pope; Anthony Chamberlain; Ranga Gunapala; et al. (Familial Cancer, 2017)

Repurposing FDA-approved drugs for anti-aging therapies - Terry W. Snell; Rachel K. Johnston; Bharath Srinivasan; Hongyi Zhou; Mu Gao; Jeffrey Skolnick (Biogerontology, 2016)

SPECT Imaging of 2-D and 3-D Distributed Sources with Near-Field Coded Aperture Collimation: Computer Simulation and Real Data Validation - Zhiping Mu; Lawrence W. Dobrucki; Yi-Hwa Liu (Journal of Medical and Biological Engineering, 2016)

QTL mapping of adult-plant resistance to stripe rust in wheat line P9897 - X. L. Zhou; D. J. Han; X. M. Chen; J. M. Mu; W. B. Xue; Q. D. Zeng; Q. L. Wang; L. L. Huang; Z. S. Kang (Euphytica, 2015)

Characterization of a Novel Two-Component System in Burkholderia cenocepacia - Callie R. Merry; Michael Perkins; Lin Mu; Bridget K. Peterson; Rebecca W. Knackstedt; Christine L. Weingart (Current Microbiology, 2015)

Intraperitoneal delivery of paclitaxel by poly(ether-anhydride) microspheres effectively suppresses tumor growth in a murine metastatic ovarian cancer model - Ming Yang; Tao Yu; Joseph Wood; Ying-Ying Wang; Benjamin C. Tang; Qi Zeng; Brian W. Simons; Jie Fu; Chi-Mu Chuang; Samuel K. Lai; T.-C. Wu; Chien-Fu Hung; et al. (Drug Delivery and Translational Research, 2014)

Apoptosis repressor with caspase recruitment domain is regulated by MAPK/PI3K and confers drug resistance and survival advantage to AML - P. Y. Mak; D. H. Mak; H. Mu; Y. Shi; P. Ruvolo; V. Ruvolo; R. Jacamo; J. K. Burks; W. Wei; X. Huang; S. M. Kornblau; M. Andreeff; et al. (Apoptosis, 2014)

Assessment of the MODIS global evapotranspiration algorithm using eddy covariance measurements and hydrological modelling in the Rio Grande basin - A. L. Ruhoff; A. R. Paz; L. E. O. C. Aragao; Q. Mu; Y. Malhi; W. Collischonn; H. R. Rocha; S. W. Running (Hydrological Sciences Journal, 2013)

Significantly differential diffusion of neuropathological aggregates in the brain of transgenic mice carrying N-terminal mutant huntingtin fused with green fluorescent protein - Pei-Hsun Cheng; Chia-Ling Li; Lu-Shiun Her; Yu-Fan Chang; Anthony W. S. Chan; Chuan-Mu Chen; Shang-Hsun Yang (Brain Structure and Function, 2013)

Increased prevalence of seizures in boys who were probands with the FMR1 premutation and co-morbid autism spectrum disorder - Weerasak Chonchaiya; Jacky Au; Andrea Schneider; David Hessl; Susan W. Harris; Meredith Laird; Yi Mu; Flora Tassone; Danh V. Nguyen; Randi J. Hagerman (Human Genetics, 2012)

Expression profiles of seven channel catfish antimicrobial peptides in response to Edwardsiella ictaluri infection - J W Pridgeon; X Mu; P H Klesius (Journal of Fish Diseases, 2012)
Using quantitative polymerase chain reaction (QPCR), the relative transcriptional levels of seven channel catfish antimicrobial peptide (AMP) genes (NK‐lysin type 1, NK‐lysin type 2, NK‐lysin type 3, bactericidal permeability‐increasing protein, cathepsin D, hepcidin and liver‐expressed AMP 2) in response to Edwardsiella ictaluri infection were determined. None of the AMP genes tested was significantly upregulated at 2 h post‐infection. Hepcidin was the only one that was significantly ( P P E. ictaluri , all lethal doses were able to induce significant ( P In vitro growth studies revealed that the presence of synthetic hepcidin peptide at a concentration of 16 μ m or higher significantly inhibited the cell proliferation of E. ictaluri . Taken together, our results suggest that hepcidin might play an important role in the channel catfish defence against E. ictaluri infection.

Modulation of high impulsivity and attentional performance in rats by selective direct and indirect dopaminergic and noradrenergic receptor agonists - Anushka B. P. Fernando; Daina Economidou; David E. Theobald; Mu-Fa Zou; Amy H. Newman; Marcia Spoelder; Daniele Caprioli; Margarita Moreno; Lucia Hipόlito; Albert T. Aspinall; Trevor W. Robbins; Jeffrey W. Dalley (Psychopharmacology, 2012)

Sequence characterization and promoter identification of porcine APC10 gene - W. B. He; Z. W. Wang; Y. Li; Z. L. Tang; S. L. Yang; Y. L. Mu; K. M. Peng; K. Li (Molecular Biology Reports, 2010)

Molecular characterization and association analysis of FBXO40 with partial hematological indexes in pig - Z. W. Wang; X. Y. Li; Z. L. Tang; S. L. Yang; Z. Z. Ying; T. Fu; B. Fan; Y. L. Mu; H. Ao; K. Li (Molecular Biology Reports, 2010)

The chromosomal localization, expression pattern and polymorphism analysis of porcine FSCN1 gene differently expressed from LongSAGE library - Zh. L. Tang; X. J. Zhang; Sh. L. Yang; Y. L. Mu; W. T. Cui; H. Ao; K. Li (Molecular Biology Reports, 2010)

Partial molecular characterization, expression pattern, polymorphism and association analysis of porcine SKP2 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. M. Peng; K. Li (Molecular Biology Reports, 2010)

Expression and SNP association analysis of porcine FBXL4 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. Li; K. M. Peng (Molecular Biology Reports, 2010)

Partial molecular cloning, characterization, and analysis of the subcellular localization and expression patterns of the porcine OTUB1 gene - T. L. Shan; Z. L. Tang; D. Z. Guo; S. L. Yang; Y. L. Mu; Y. H. Ma; W. J. Guan; K. Li (Molecular Biology Reports, 2009)

Neuropsychiatric disorders related to interferon and interleukins treatment - Aye Mu Myint; Markus J. Schwarz; Harry W. M. Steinbusch; Brian E. Leonard (Metabolic Brain Disease, 2009)

Expression and immunogenicity of an Escherichia coli K99 fimbriae subunit antigen in soybean - Kenneth J. Piller; Thomas E. Clemente; Sang Mu Jun; Cynthia C. Petty; Shirley Sato; David W. Pascual; Kenneth L. Bost (Planta, 2005)

First records of the papaya strain of Papaya ringspot virus (PRSV-P) in French Polynesia and the Cook Islands - R. I. Davis; L. Mu; N. Maireroa; W. J. Wigmore; M. Grisoni; M. F. Bateson; J. E. Thomas (Australasian Plant Pathology, 2005)

Use of new EST markers to elucidate the genetic differences in grain protein content between European and North American two-rowed malting barleys - M. Moralejo; J. S. Swanston; P. Muoz; D. Prada; M. Ela; J. R. Russell; L. Ramsay; L. Cistu; P. Codesal; A. M. Casas; I. Romagosa; W. Powell; et al. (Theoretical and Applied Genetics, 2004)